THE STAKEHOLDERS’ AWARENESS AND PERCEPTION OF MALAYSIAN COMPETITION ACT 2010 AND THE ROLE PLAYED BY THE MALAYSIAN COMPETITION COMMISION - Hasnah Haron; Ishak Ismail; Yuvaraj Ganesan; Sasikala Sankaran; Idris Gautama So (Bina Nusantara University, 2018)
The Malaysian Competition Commission (MyCC) was mandated in 2010 to provide and engaged with stakeholders across all levels in promoting the Competition Act 2010 (CA 2010). This study aroused from the need to conduct a comparative study to its earlier 2013 Baseline Study in ascertaining MyCC’s effectiveness in carrying out its role in advocacy work. Therefore, the study’s main objective is to examine whether the level of awareness and perception of CA 2010 has increased over time. Other issues examined were (i) quality of advocacy and outreach of MyCC, (ii) the level of awareness and knowledge of the various stakeholders of the CA 2010 and of the role of MyCC and (iii) the perception of stakeholders on the effectiveness (quality) of enforcement of MyCC. 463 respondents participated through e-survey. 48 participated in four FGDs that took place nationwide. Results indicated overall level of knowledge on the existence of MyCC and CA 2010 is very high among SMEs compared to 2013 Baseline Study. SMEs are also the highest stakeholder group in acknowledging on the quality of MyCC’s advocacy and outreach programs. Practitioners (lawyers and economists) show the highest awareness level of CA 2010. Consumers/Trade Associations show the highest awareness level of MyCC’s role. SMEs, the highest stakeholder group in acknowledging the effectiveness (quality) of MyCC’s enforcement. Practitioners(law & economists) acknowledged that Malaysia businesses are run by only a few large players with not enough competition. The business entities (MNCs, SMEs and GLCs) indicate having good and positive practices, attitude and culture of Compliance with the CA 2010. In summary, it shows that the effectiveness of MyCC role in promoting he CA 2010 to the Malaysians.